2017
DOI: 10.9790/0853-1606092730
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cbct in Periodontics

Abstract: Diagnosis of periodontal disease mainly depends on clinical signs and symptoms. However, in the case of bone destruction, radiographs are valuable diagnostic tools as an adjunct to the clinical examination. Two dimensional periapical and panoramic radiographs are routinely used for diagnosing periodontal bone levels. In two dimensional imaging, evaluation of bone craters,lamina dura and periodontal bone level is limitedby projection geometry and superimpositions of adjacent anatomical structures. These limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…By creating a phantom model with artificial periodontal ligament space, Ozmeric et al evaluated the relationship between CBCT and conventional radiographs and discovered that the periapical radiographs were superior to CBCT for evaluating periodontal ligament space [10]. In contrast, another in vitro study found that CBCT was better than conventional radiography in visualizing the periodontal ligament space [1]. Nimish Prakash, however demonstrated that CBCT images were equally capable of demonstrating LD(lamina dura) as periapical radiographs and that coronal sections of the CBCT should be used for anterior teeth and sagittal section in the posterior teeth would be beneficial [12].…”
Section: Austin Publishing Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…By creating a phantom model with artificial periodontal ligament space, Ozmeric et al evaluated the relationship between CBCT and conventional radiographs and discovered that the periapical radiographs were superior to CBCT for evaluating periodontal ligament space [10]. In contrast, another in vitro study found that CBCT was better than conventional radiography in visualizing the periodontal ligament space [1]. Nimish Prakash, however demonstrated that CBCT images were equally capable of demonstrating LD(lamina dura) as periapical radiographs and that coronal sections of the CBCT should be used for anterior teeth and sagittal section in the posterior teeth would be beneficial [12].…”
Section: Austin Publishing Groupmentioning
confidence: 99%
“…As bone loss is an inevitable feature of periodontitis, radiographs are a valuable tool as an adjunct to clinical examination. The most commonly used; periapical and panaromic radiographs, have several limitations such as [1] the 2 dimensional natures of the image, distortion and magnification of the X-rays, and super-imposition of adjacent anatomical structure. Therefore bony defects on buccal and lingual sides / furcation involvements and root concavities to go un-noticed.…”
Section: Introductionmentioning
confidence: 99%